Implementasi Kurikulum Pesantren Leadership Daarut Tarqiyah Primago dalam Mempersiapkan Calon Santri Menuju Pondok Modern Gontor - Minda Mahira (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to analyze the implementation of the curriculum at Pesantren Leadership Daarut Tarqiyah Primago and its impact on prospective students’ readiness for the admission selection of Pondok Modern Darussalam Gontor. This research employs a qualitative approach with a case study design to gain an in-depth understanding of the learning processes and student development within the pesantren context. Data were collected through observations, semi-structured interviews, and documentation. The data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation as well as member checking.The findings reveal that the curriculum implementation at Pesantren Leadership Daarut Tarqiyah Primago is designed integratively by combining academic instruction, character building, foreign language reinforcement, and leadership training. Structured learning programs, including discipline habituation, religious practices, and intensive training for entrance examinations, have proven effective in enhancing students’ cognitive, affective, and psychomotor readiness. Furthermore, a supportive learning environment and the active role of educators significantly contribute to the success of the program. However, several challenges were identified, including limited training time and the diverse initial competencies of students, which affect the effectiveness of the learning process. Therefore, curriculum innovation that is more adaptive and responsive to students’ needs is necessary. Overall, the leadership-based curriculum implemented in this pesantren demonstrates strong potential as an alternative educational model for preparing students to succeed in the admission process of modern Islamic educational institutions.